QUESTIONS OF TUTORING WORK - E N Kovaleva; D A Vasiliev; S N Zolotukhin (Erudio Journal of Educational Innovation, 2018)
In the article elements of tutor's work as pedagogical activity on individualization of education aimed at revealing and developing the student's interests, searching for resources for creating an individual educational program, forming the student's educational reflection, are considered.